OPTIMALISASI PENGOLAHAN SAMPAH ORGANIK DENGAN TEKNOLOGI BIODIGESTER SEBAGAI UPAYA KONSERVASI LINGKUNGAN - Redaksi Tim Jurnal (KILAT, 2017)
Garbage is one of important issues in the life community, particularly in Indonesia. The volume of garbage heap is increasing along with the increase of public consumption every day, which affects garbage accumulation especially in GEMPEL - BEHI TPST. Therefore, an alternative waste treatment is needed to reduce the volume of waste to be transported to the landfill by utilizing organic waste with anaerobic-digester technology. This condition encourages researchers to design biodigester type fixed dome to optimize waste processing. Based on the research that has been done, Designed anaerobic-digester that had been made can be known the total volume of reactor used is 196,8 m3 to process waste 32,8m3/day. From utilization the anaerobic-digester technology, it provides benefits for the community such as income from the sale of economic value of waste are Rp. 58.795.750,- per month and value of expenses are Rp 52.320.000,- per month with pay back period are 6 month. So with the design, it occurs environmental conservation efforts as one step to improve human welfare and realize the sustainability of natural resources.